Edukasi Peran Fisioterapi dalam Manajemen Diastasis Recti pada Komunitas Ibu Hamil di Puskesmas Lolo Kalimantan Timur - Fajar Abhyasa Abimanyu; Rakhmad Rosadi; Herlina (Rena Cipta Mandiri, 2025)
Diastasis recti abdominis (DRA) is a condition characterized by the separation of the rectus abdominis muscles greater than 2.5 cm due to abdominal wall stretching during pregnancy. This condition can lead to impaired trunk stability, postural changes, and back pain in postpartum women. Physiotherapy plays an essential role in managing DRA through strengthening exercises for the transversus abdominis (TrA) and pelvic floor muscles (PFM), core stability training, and the use of supportive aids such as elastic binders to increase intra-abdominal pressure and enhance abdominal muscle stability. This study aims to improve pregnant women's understanding of DRA through education and self-exercise programs at the Maternal Health Posyandu in Keluang Lolo Village, Janju Village, and Sempulang Village, Kuaro District, Paser Regency, East Kalimantan. The method used in this activity was educational counseling through leaflet distribution and direct demonstrations. Evaluation was conducted by comparing pre-test and post-test results to measure participants' understanding improvement. The results showed a significant increase in knowledge, with the majority of participants initially having low understanding, progressing to higher comprehension after the education session. This educational activity proved effective in enhancing pregnant women's awareness of the role of physiotherapy in DRA management and how to perform self-exercises at home.